2023
DOI: 10.1038/s41598-023-30326-3
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic effects of bilingualism on brain structure map onto general principles of experience-based neuroplasticity

Abstract: Bilingualism has been linked to structural adaptations of subcortical brain regions that are important for controlling multiple languages. However, research on the location and extent of these adaptations has yielded variable patterns, especially as far as the subcortical regions are concerned. Existing literature on bilingualism-induced brain restructuring has so far largely overseen evidence from other domains showing that experience-based structural neuroplasticity often triggers non-linear adaptations whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 62 publications
1
6
0
Order By: Relevance
“…The caudate nucleus may thus be the fastest subcortical structure to optimise and renormalise in volume due to its integral role in language control. This coincides with recent studies showing a pattern of expansion followed by contraction of the caudate nucleus with increasing L2 immersion (DeLuca et al, 2019a;Korenar et al, 2023;Marin-Marin et al, 2022). The authors of these studies suggested that greater automation has occurred in language monitoring and selection, allowing the caudate nucleus to return to a baseline volume.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The caudate nucleus may thus be the fastest subcortical structure to optimise and renormalise in volume due to its integral role in language control. This coincides with recent studies showing a pattern of expansion followed by contraction of the caudate nucleus with increasing L2 immersion (DeLuca et al, 2019a;Korenar et al, 2023;Marin-Marin et al, 2022). The authors of these studies suggested that greater automation has occurred in language monitoring and selection, allowing the caudate nucleus to return to a baseline volume.…”
Section: Discussionsupporting
confidence: 89%
“…Subcortical effects in the form of larger volumes in the caudate nucleus, putamen, globus pallidus, and thalamus have been observed in bilinguals when compared with monolinguals (Burgaleta et al, 2016;Pliatsikas et al, 2017). When compared with monolinguals or bilinguals with limited language experiences, bilinguals with higher language immersion have presented with a lack of cortical effects, and/or with contractions in the caudate nucleus, nucleus accumbens and thalamus (Costumero et al, 2020;DeLuca et al, 2019a;Korenar et al, 2023;Pliatsikas et al, 2017). In conjunction with subcortical effects, there has been corroborating evidence from studies on white matter effects in bilingual adults and children (for a review see Li et al, 2014).…”
Section: Bilingualism and Brain Adaptationsmentioning
confidence: 99%
See 2 more Smart Citations
“…interhemispheric information ow and cortico-subcortical connectivity (DeLuca et al, 2019, 2020; Morgan-Short et al, 2022; Morgan-Short & Ullman, 2022; Pliatsikas et al, 2017; Ullman, 2020).In line with this theory, (Korenar, Treffers-Daller, & Pliatsikas, 2021) demonstrated how bilingual experiences induce dynamic structural changes in the caudate and thalamus (see alsoKorenar et al, 2023). These areas, which have been extensively studied in both healthy and clinical populations, are known to play a crucial role in language control processes (see alsoDeLuca et al, 2019DeLuca et al, , 2020Pliatsikas et al, 2017).…”
mentioning
confidence: 86%